First assessment of floating marine litter abundance and distribution in the Bay of Biscay from an integrated ecosystem survey. (January 2022) - Ruiz, Irene; Burgoa, Iñaki; Santos, María; Basurko, Oihane C.; García-Barón, Isabel; Louzao, Maite; Beldarrain, Beatriz; Kukul, Deniz; Valle, Claudia; Uriarte, Ainhize; Rubio, Anna
Abstract: In the Bay of Biscay, regional monitoring programmes and data on abundance and distribution of floating marine litter are scarce, contrary to many other European marine regions. Here, a joint analysis of multiyear observations (2017–2019) of floating micro and macrolitter and oceanographic conditions was conducted for the Bay of Biscay by combining microlitter samplings with neuston nets and vessel-based macrolitter observations. Results show spatiotemporal abundance and distribution patterns. The density of floating microlitter increased from 26, 056 items/km 2 in 2017 to 1, 802, 4611 items/km 2 in 2019; floating macrolitter densities barely varied amongst year (2.52 items/km 2 in 2017 and 3.70 items/km 2 in 2019). No significant correlation was found between densities of micro and macrolitter, neither for the oceanographic variables. We conclude that longer micro and macrolitter monitoring periods and standardized datasets based on the cross-border cooperation are needed to collect more comparable information, evaluate trends, and support decision making in the area. Highlights: A combined assessment of macro and microlitter was done for the Bay of Biscay. An average of 3.13 (macro) and 756, 865 (micro) items/km 2 were observed. Packaging, other plastic items and plastic bottles were the most abundant items. No correlation between densities and oceanographic variables was observed. Integrated ecosystem surveys are a good platform for monitoring marine litter.